Assessing economic performance : some features of British economic development 1950-1965 in the light of economic theory and the principles of economic planning - Lipton, Michael (London : Staples Press, 1968)
The book focused on the features of British economic development 1950-1965 in the light of economic theory and the principles of economic planning. After a general introduction in chapter 1, the aims of British economic policy (growth, full employment, price stability, income re-distribution) are discussed in in Chapter 2. The next chapter assesses the performance of the UK in recent years under each of the same headings. Finally, Chapter 4 analyses the statistical relationships between the various policy aims on the basis of a large number of simple, multiple and partial correlation coefficients.
Includes index.
Includes bibliographical footnotes.
lje 07/05/2018
Loans
Keywords: Economics; Economic situation; Great Britain